Drawing skills at the beginning of higher education: Teachers’ perspectives, expectations, and realities - da Silva, Pedro Ramalho; Palaré, Odete (Frontiers in Education, 2023)
For more than two decades, educational policies in Portugal have primarily focused on improving student outcomes, reducing school absenteeism, and preventing school abandonment. Another factor has been the overemphasis on literacy and numeracy, which has resulted in an unbalanced weighting of these school subjects on instructional time. As a result, instruction time for non-essential classes, such as music and visual arts, was reduced. What effect do these policies have on the drawing abilities and visual literacy of those who pursue visual arts studies in higher education? To date, there has been a plethora of studies on drawing in its didactic, neurological, and physiological components, with findings that strengthen and support the idea that drawing plays a central role in the development of conceptual thinking and abductive reasoning (Simmons, 2019). That is significant in advocating for drawing as a learning tool in S.T.E.M., but also, for drawing to play a different role in education overall (Kantrowitz et al., 2017). To determine whether these policies impact the competencies, skills, and visual literacy of those who pursue visual arts studies, we surveyed higher education teachers regarding their perceptions of student drawing skills as they begin college degrees ranging from fine arts to design. Some survey findings point to weak areas, particularly in perspective drawing and preparatory drawings and sketches. The teachers' suggested causes were mostly political. These findings should be investigated further, specifically through follow-up interviews and a survey of first- and second-year students enrolled in the courses taught at the educational institutions under analysis.